Experimental and finite element analysis of bond-slip in reinforced concrete - Wolenski, A. R. V.; Castro, S. S. De; Penna, S. S.; Pitangueira, R. L. S.; Silva, B. V.; Barbosa, M. P. (IBRACON - Instituto Brasileiro do Concreto, 2015)
The modeling of reinforced concrete structures has taken advantage of the increasing progress on Computational Mechanics, in such way that complex phenomena, such as cracking and crushing, creep, reinforcement yielding, steel-concrete bond loss, can be modeled in a reasonable realistic way, using the proper set of numerical and computational resources. Among several options, the ones based on the Finite Element Method (FEM) allow complex analysis simulations of reinforced concrete structures, including the interaction of different nonlinear effects. This paper deals with the nonlinear finite element analysis of the bond-slip between reinforcing steel and concrete, taking into account an experimental study previously performed. The FEM analysis presented uses a combination of resources where the material behavior of concrete is described by the Microplane Constitutive Model, and an embedded reinforcement model is used to represent steel inside the concrete and take into account the effect of bond-slip. The FEM models were created using the INSANE (INteractive Structural ANalysis Environment) computational system, open source software that has a set of FEM tools for nonlinear analysis of reinforced concrete structures. The correlations between numerical-experimentals results and several parameters validate the proposed combination of resources and identifies the significance of various effects on the response.

A modelagem de estruturas de concreto armado tem tido um crescente progresso na Mecânica Computacional, de modo que os fenômenos complexos, tais como fissuração e esmagamento, fluência, escoamento da armadura, perda da aderência aço-concreto, podem ser modelados de forma razoavelmente realista, usando um conjunto apropriado de recursos numéricos e computacionais. Entre as diversas opções, os baseados no Método dos Elementos Finitos (MEF) permitem simulações complexas de análises de estruturas de concreto armado, incluindo a interação de diferentes efeitos não lineares. Este artigo lida com a análise não linear em elementos finitos, da perda de aderência entre a armadura de aço e o concreto, levando em consideração um estudo experimental anteriormente realizado. A análise via MEF apresentada usa uma combinação de recursos onde o comportamento do concreto é descrito pelo Modelo Constitutivo de Microplanos, e um Modelo de Armadura Embutida é usado para representar o aço inserido no concreto e levar em conta o efeito da perda de aderência. Os modelos do MEF foram criados usando o sistema computacional INSANE (Interactive Structural Analysis Environment), software de código aberto que possui um conjunto de ferramentas para análise não linear de estruturas em concreto armado. As correlações entre os resultados numérico-experimentais e os vários parâmetros validam a combinação de recursos proposta e identificam o significado de vários efeitos sobre a resposta.
Análises experimental e por elementos finitos da perda de aderência em concreto armado
Keywords: reinforced concrete structures; microplane constitutive models; embedded reinforcement; bond-slip; estruturas de concreto armado; modelos constitutivos de microplanos; armadura embutida; perda de aderência